Taking VANET to the clouds - Olariu, Stephan; Ismail, Khalil; Abuelela, Mahmoud (International journal of pervasive computing and communications, 2011)
Purpose - The past decade has witnessed a growing interest in vehicular networking and its myriad applications. The initial view of practitioners and researchers was that radio-equipped vehicles can keep the drivers informed about potential safety risks and can enhance their awareness of road conditions and traffic-related events. This conceptual paper seeks to put forth a novel vision, namely that advances in vehicular networks, embedded devices, and cloud computing can be used to set up what are known as vehicular clouds (VCs). Design/methodology/approach - The paper suggests that VCs are technologically feasible and that they are likely to have a significant societal impact. Findings - The paper argues that at least in some of its manifestations, the ideas behind VCs are eminently implementable under present day technology. It is also expected that, once adopted and championed by municipalities and third-party infrastructure providers, VCs will redefine the way in which pervasive computing and its myriad applications is thought of. Research limitations/implications - This is a new concept for which a small-scale prototype is being built. No large-scale prototype exists at the moment. Practical implications - VCs are a novel concept motivated by the realization of the fact that, most of the time, the tremendous amount of computing and communication resources available in vehicles is underutilized. Putting these resources to work in a meaningful way should have a significant societal impact. Social implications - The main goal of this paper is to introduce and promote the concept of VCs, a non-trivial extension, along several dimensions, of the by-now "classic" cloud computing. The paper shows that the concept of VCs is feasible as of today - at least in some of its manifestations - and that it can have a significant societal impact in the years to come. Originality/value - The idea of a VC is novel and so are the potential applications that are discussed in the paper.